"دور المهارات الناعمة في الأداء الوظيفي في المؤسسات الخدماتية - دراسة تطبيقية في الوكالة السياحية " - عبد المالك مرغم; خليل هيشور; هشام دجال (جامعة الوادي university of eloued, 2024)
" إن المهارات الناعمة هي مهارات شخصية نفسية تتعلق بسلوك الفرد لذا هي غير قابلة للضبط والقياس. المهارات الناعمة لها عدة أبعاد نذكر منها: مهارات الاتصال والتواصل، مهارة العمل ضمن الفريق والتفاوض، مهارة القدرة على القيادة واتخاد القرارات كذلك مهارات إدارة الوقت وإدارة الأزمات. وبناء على دراستنا واختبار الفرضيات وجدنا: - يوجد أثر ذو دلالة احصائية للمهارات الناعمة في تحسين الأداء الوظيفي لموظفي وكالة رزاق هبلة للسياحة والاسفار عند مستوى دلالة (0.05). - لا يوجد أثر ذو دلالة إحصائية عند مستوى معنوية (0.05) بين بعد الاتصال والتواصل والأداء الوظيفي لموظفي وكالة رزاق هبلة للسياحة والاسفار. - لا يوجد أثر ذو دلالة إحصائية عند مستوى معنوية (0.05) بين بعد إتخاذ القرار وحل المشكلات والأداء الوظيفي لموظفي وكالة رزاق هبلة للسياحة والاسفار. - يوجد أثر ذو دلالة إحصائية عند مستوى معنوية (0.05) بين بعد العمل ضمن الفريق والأداء الوظيفي لموظفي وكالة رزاق هبلة للسياحة والاسفار. - يوجد ذو دلالة إحصائية عند مستوى معنوية (0.05) بين بعد إدارة الوقت والأداء الوظيفي لموظفي وكالة رزاق هبلة للسياحة والاسفار. " "Soft skills are personal psychological skills related to an individual's behavior and cannot be controlled or measured. Soft skills have several dimensions, including: communication and communication skills, the skill of working within a team and negotiation, the ability to lead and make decisions, time management and crisis management skills. Based on our study and hypothesis testing, we found: - There is a statistically significant effect of soft skills in improving the job performance of employees of the Habla Tour Agency in El Oued State at a significance level of (0.05) - There is no statistically significant effect at a significant level (0.05) between the communication dimension and the job performance of the employees of the Habla Tour Agency in the state of El Oued. - There is no statistically significant effect at a significance level (0.05) between the dimension of decision-making and problem-solving and the job performance of the employees of the Habla Tour Agency in the state of El Oued. - There is a statistically significant effect at a significant level (0.05) between the dimension of working within a team and the job performance of the employees of the Habla Tour Agency in the state of El Oued. - There is a statistical significance at the level of significance (0.05) between the time management dimension and the job performance of the employees of the Habla Tour Agency in the state of Al-Wadi. "
Keywords: المهارات الناعمة - الأداء الوظيفي - الاتصال والتواصل - إدارة الوقت. soft skills - job performance - communication and communication - time management.